Pengaruh Organizational Culture dan Job Involvement terhadap Employee Commitment di Perum Perhutani KPH Sukabumi - Ardi M Noer; Anisa Dahyanti (Cakrawala Repositori IMWI, 2018)
Perum Perhutani KPH Sukabumi is a State-Owned Enterprise formed as a Public Company (Perum) with the duty and authority to manage the state forest resources located in Java and Madura Island, with the aim to know the influence of Organizational Culture And Job Involvement Against Employee Commitment on Perum Perhutani KPH Sukabumi. Design: the method used in this study is by survey method and menggunaka questionnaire as a tool which then disseminated to 70 respondents. While the techniques in this study using the test instrument consisting of validity and reliability test, and on data analysis techniques using correlation and descriptive analysis. In addition, the hypothesis testing of the authors is done by using multiple linear regression analysis. Result: based on the results of its output stated that the Organizational Culture variables have a significant influence on the Employee Commitment, as well as the independent variable Job Involvement which has significant value to the Employee Commitment. Both variables have a positive effect on Employee Commitment